Membangun Kurikulum Cinta dalam Pembelajaran Bahasa Arab: Quo Vadis Pendidikan Karakter di Era Digital - Muhammad Rido'i; Muhammad Tareh Aziz (LPPM UNISDA, 2026)
This study aims to examine the urgency and relevance of the Love Curriculum in Arabic language learning as an effort to strengthen character education in the digital era. The rapid advancement of information technology has significantly transformed the learning process; however, it has also given rise to challenges such as increasing intolerance, the spread of hate speech, radicalism, and the erosion of humanitarian values among students. These conditions necessitate curriculum innovation that emphasizes not only the development of academic competencies but also the cultivation of character grounded in the values of compassion, tolerance, moderation, and respect for diversity. This study employed a qualitative approach using a library research design. Data were collected from primary and secondary sources, including books, scholarly journal articles, official documents issued by the Indonesian Ministry of Religious Affairs, and previous studies related to the Love Curriculum, Arabic language learning, character education, and educational transformation in the digital era. The data were analyzed using content analysis through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the Love Curriculum has a high level of urgency in Arabic language learning because it integrates language proficiency with the internalization of character values such as empathy, tolerance, cooperation, and respect for differences. Furthermore, the Love Curriculum is highly relevant in the digital era as it promotes the meaningful use of educational technology while maintaining the affective and moral dimensions of learning. Therefore, the Love Curriculum represents a strategic alternative for fostering humanistic, inclusive, and character-oriented Arabic language learning that aligns with the vision of a moderate, civilized, and nationally oriented education system.